Effect of Manure and Inorganic Fertilizers on Vegetative, Generative Characteristics, Nutrient, and Secondary Metabolite Contents of Mungbean - Sutrisno Sutrisno; Eriyanto Yusnawan (Biosaintifika: Journal of Biology & Biology Education)
A field experiment was conducted in the upland of Muneng Probolinggo during early dry season (April – June 2015) to study the effect of manure and inorganic fertilizers on vegetative, generative growth, nutrient, and secondary metabolite contents of mungbean (Vigna radiata L.). The treatments consisted of (1) no fertilizer, (2) 10.4, 18, 60 kg of N, P, K ha-1, (3) 22.5: 22.5: 22.5 kg of NPK ha-1, (4) 5000 kg ha-1 manure, and (5) 11.25:11.25:11.25 kg of NPK ha-1 + 2500 kg ha-1 manure. These treatments were arranged in a randomized completely block design with three replications. Application of manure, inorganic fertilizer, and its combination significantly stimulated several vegetative characters especially number of nodes, number of clusters, fresh weight of biomass, and number of nodules. At the generative characters, application of manure and inorganic fertilizers also significantly increased pod dry weight and grain dry weight. Among all treatments, NPK inorganic fertilizer (T2) gave the highest vegetative and generative growth which was shown on biomass fresh weight, pod dry weight and grain dry weight per plant. NPK fertilizer and manure applications increased total flavonoid and phenolic contents as well as antioxidant activity. This combination treatment therefore, could be suggested in mungbean cultivation to increase seed quality.